UPAYA PEMENUHAN HAK PEKERJA/BURUH PERSPEKTIF UNDANG-UNDANG NOMOR 21 TAHUN 2000 TENTANG SERIKAT PEKERJA DAN PERMASALAHANNYA: Efforts To Fulfill Workers’ Rights From The Perspective Of Law Number 21 Of 2000 Concerning Trade Unions And Their Problems - Asmawardhani, Dewi; Suryaningsih, Baiq Nur Aini Dwi; Aminullah, Aminullah (Ganec Swara, 2025)
Worker/laborer is every person who works by receiving wages or other forms of compensation." who can fight for their rights by forming a trade union in the company where they work as regulated in Law Number 21 of 2000 concerning Worker Unions. The aim of this research is to determine efforts to fulfill worker/labor rights and the problems in their implementation. By using normative research methods, it is hoped that the research results can be used as a solution as an effort to improve the welfare of workers/laborers by entering into a Collective Labor Agreement between workers and the company where they work, and fighting for workers’ rights to negotiate. The existence of internal and external obstacles is a problem that a solution must be found, and if there is a dispute it should be resolved by deliberation and consensus. The government is expected to continue to carry out outreach, especially regarding regulations in the field of employment.